HISTORICAL AND LEGAL ANALYSIS OF KNOWLEDGE ABOUT THE CONCEPT “CONSTITUTIONAL REGULATION” - Nurmagambetov , Рашит Габитович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2018)
The article presents a historical and legal analysis of the evolution of the authors ' positions on the concept of constitutional regulation. Based on the analysis of different points of view, the author examines the features of the development of scientific knowledge about the concept of constitutional regulation in the Soviet and modern periods of the Russian state. Adhering to the position that as a scientific category constitutional regulation is a relatively "new" term of legal science in Russia, exploring the development of scientific knowledge about this phenomenon shows the evolutionary way of filling its content with scientific knowledge. Particular attention is paid to the analysis of the modern period of development of theoretical and legal knowledge of constitutional regulation, the justification of its place among other categories of science of constitutional law. Analyzing the position of the authors on the development of the concept of constitutional regulation in the new socio-economic and political-legal reality, the author concludes that there is no theoretical discussion among the constitutionalists on this issue, which raises the problem of clarifying the concept of constitutional regulation, the exhaustive definition of which was proposed by representatives of the Soviet legal science. According to the author, the purpose of constitutional regulation for a long historical period of its theoretical design does not change. The changes have affected its content. They are due to the evolutionary development of the Russian state, the transformation of its form, which is reflected in the Constitution. This caused an objective expansion of the existing system of legal knowledge about the constitutional regulation and set the task of work on its substantive deepening as a scientific category, actualization of its understanding as a necessary constitutional tool that has a political and legal impact on new types of social relations.